1992
DOI: 10.1007/bf02091901
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal perspective on adolescent substance abuse

Abstract: The links between adolescent substance abuse and adult alcohol and drug misuse and dependence are now well established. The vast majority of adult substance misusers start in their adolescent years. This, and the emotive nature of adolescent substance abuse generated an increased and justifiable interest in substance abuse in adolescent populations, that began in the early 1970s. This paper reviews the most relevant recent literature relating to the subject especially that which had a longitudinal design. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 83 publications
1
10
1
Order By: Relevance
“…Previous research in general populations describes early drinking as a risk factor for later alcohol dependence(31) and continued alcohol use. (32) However, this study shows that early drinking among survivors is even more predictive of later heavy drinking than among a general population sample. Despite often increased parental supervision and increased health concerns, those survivors who initiate drinking at a young age may be especially motivated to do so, and may be turning to alcohol out of anger or distress related to the diagnosis, treatment or other related family or social problems that were heightened in the context of cancer.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous research in general populations describes early drinking as a risk factor for later alcohol dependence(31) and continued alcohol use. (32) However, this study shows that early drinking among survivors is even more predictive of later heavy drinking than among a general population sample. Despite often increased parental supervision and increased health concerns, those survivors who initiate drinking at a young age may be especially motivated to do so, and may be turning to alcohol out of anger or distress related to the diagnosis, treatment or other related family or social problems that were heightened in the context of cancer.…”
Section: Discussioncontrasting
confidence: 56%
“…(31, 32) It is unclear whether these risk factors apply equally to cancer survivors. Cancer-related risk factors have been less explored but knowledge of these factors is equally crucial to improve early identification of survivors at elevated risk for heavy drinking.…”
Section: Introductionmentioning
confidence: 99%
“…In 1994 the second most commonly mentioned reason was “for kicks, for fun, to feel good,” which replaced “because friends do, trendy.” Pupils continue to see social and peer group pressures as the main influences on a decision to start taking drugs, a view endorsed by Swadi 13. The perception that drugs are taken “for kicks, for fun” shows that these young people are aware that drugs do have pleasurable effects, a point often ignored by educationalists.…”
Section: Discussionmentioning
confidence: 99%
“…Family background and parenting styles have been found to predict later adolescent drug misuse 13. Some drug prevention teams funded by the Home Office have successfully worked with “parent empowerment” groups.…”
Section: Discussionmentioning
confidence: 99%
“…Rohde et al, (1996) found that more than 80% of adolescents with alcohol abuse or dependency had some other form of psychopathology and that alcohol disorders in general followed rather than preceded the onset of other psychiatric disorders. Swadi (1992) concludes on the basis of reviewed studies that emotional symptoms of psychiatric disturbance are more likely to precede substance abuse, and that behavioral symptoms are more likely to coincide with or follow it. Weill and Le Bourhis (1994) noted that the heaviest drinkers in young adulthood were generally dissatisfied with life, unconstrained, and pessimistic five years earlier.…”
mentioning
confidence: 99%